A RARE CLINICAL CASE OF MIXED SEROUS NEUROENDOCRINE CYSTIC NEOPLASM OF THE PANCREAS - A. P. Koshel; V. V. Alipov; L. R. Bazilevich; A. I. Khvashchevsky; I. L. Purlik; E. S. Drozdov (Сибирский онкологический журнал)
Background. Serous cystic pancreatic neoplasm is a rare pancreatic tumor, accounting for 1–2 % of all pancreatic tumors. In 2010,  mixed serous neuroendocrine cystic neoplasia was included into the classification of the WHO for pancreatic tumors. Only a few cases of this disease have been reported in the literature. Mixed serous  neuroendocrine cystic neoplasia is often associated with von Hippel  Lindau disease. Most authors recommend surgery as a main treatment of this disease.Case report. We present a case with mixed serous neuroendocrine  cystic neoplasia not associated with von Hippel Lindau disease. The  patient underwent spleen – preserving distal pancreas resection. The diagnosis was histologically and immunohistochemically  verified. There is no evidence of disease recurrence within 10  months after surgery. Conclusion. Histological examination of the  resected serous cystadenoms should take into account the possibility of combining this pathology with pancreatic neuroendocrine tumors.  For the purpose of verification, the use of immunohistochemical  examination is required. Radical surgical resection allows patients  with this disease to be cured.